Análise da acessibilidade nas calçadas do bairro Jardim Tropical I, no município de Campo Mourão – PR - Damazio, Murilo (2014)
Every human been has the right to equality and security, warranted by the constitution. To walk is one of the most usual activities performed by any person, however for this to be possible, it is necessary that the sidewalks accord several requirements to be accessible, namely, to ensure that any pedestrian use them with security, comfort and autonomy. Accessibility is important because not all users have physical condition to walk on a sidewalk full of holes, for example, the IBGE in 2010 appointed that 35.7 million brazilians have difficulty to see and other 13.2 million people with motor deficiency. The goal of this work was to analyze the accessibility on sidewalks of the Jardim Tropical I neighborhood, in the city of Campo Mourão - PR. Projects of type C standard sidewalks and paving of Tropical Garden I neighborhood (that includes the project of accessible sidewalks) were analyzed, both located in Campo Mourão. A field work was also done, analyzing the accessibility of sidewalks in the neighborhood. With a tape measure, ruler and level tube, it was possible to collect data and analyze the following items: breadth, inclinations, coating, tactile signage, car ramp, accessible ramps. All collected data were compared with the search results. Owing to the large number of items analyzed and compared, it is complicated show all results here. The two projects presented nonconforming items, the corrections can be made and must be made, some more easily, like putting tactile signage, others less so, such as implantation of access ramps for cars correctly. Was found a serious problem with trees that prevented the execution of sidewalks in some places, this could be avoided with more detailed study of the site.